2021
DOI: 10.1186/s12967-021-02915-1
|View full text |Cite
|
Sign up to set email alerts
|

ELK4 promotes the development of gastric cancer by inducing M2 polarization of macrophages through regulation of the KDM5A-PJA2-KSR1 axis

Abstract: Background We tried to elaborate the molecular mechanism of ETS-like transcription factor 4 (ELK4) affecting gastric cancer (GC) progression through M2 polarization of macrophages mediated by lysine-specific demethylase 5A (KDM5A)-Praja2 (PJA2)-kinase suppressor of ras 1 (KSR1) axis. Methods GC expression dataset was obtained from GEO database, and the downstream regulatory mechanism of ELK4 was predicted. Tumor-associated macrophages (TAMs) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…These TFs in macrophages are newly discovered and may affect NOA. GSVA enrichment analysis of tMΦ in normal persons and iNOA patients showed that tMΦ of iNOA patients was significantly enriched in the proliferation pathway, which also indicated that thetMΦ of iNOA patients was overproliferated, which was consistent with the previous research results of Wenzhong Zheng ( Zheng et al, 2021 ). The changes of TFs activity found in iNOA tMΦ may regulate the development and function of tMΦ and the differentiation of tM into M2 macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…These TFs in macrophages are newly discovered and may affect NOA. GSVA enrichment analysis of tMΦ in normal persons and iNOA patients showed that tMΦ of iNOA patients was significantly enriched in the proliferation pathway, which also indicated that thetMΦ of iNOA patients was overproliferated, which was consistent with the previous research results of Wenzhong Zheng ( Zheng et al, 2021 ). The changes of TFs activity found in iNOA tMΦ may regulate the development and function of tMΦ and the differentiation of tM into M2 macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the influence of AS-tDR-007333-HSPB1-histone modification axis on MED29 gene expression, we also found that AS-tDR-007333 stimulated the expression of ELK4 to enhance the activity of MED29 promoter. ELK4 is a transcription factor belonging to the ternary complex factor subfamily of E twenty-six domain transcription genes [ 41 ]. ELK4 has been identified as a proto-oncogene whose overexpression was associated with the malignant phenotypes of prostate, melanoma, and gastric cancers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The network markers indicated that endothelium, oxidative stress, and inflammation have important roles in atherosclerosis; the top-ranked genes (by degree) and their corresponding functions are shown in Table 4 ( Yang et al, 2000 ; Zhang, 2013 ; Schisler et al, 2015 ; Mezzadra et al, 2017 ; Zheng et al, 2017 ; Guan et al, 2018 ; Lan et al, 2020 ; Nie et al, 2020 ; Zheng et al, 2020 ; Chen et al, 2021a ; Cao et al, 2021 ; Covarrubias et al, 2021 ; Liu et al, 2021 ; Wang et al, 2021 ; Zheng et al, 2021 ). For example, the gene with the largest degree was PXN, which encodes a cytoskeleton protein.…”
Section: Resultsmentioning
confidence: 99%